Food profile of Yanomami indigenous children aged 6 to 59 months from the Brazilian Amazon, according to the degree of food processing: a cross-sectional study - Moraes, Aline Oliveira dos Santos (2022)
Federal University of Pelotas. Postgraduate Program in Nutrition and Food. Pelotas, RS, Brazil.